Analysis of the linear dimensions of the high stability alginate cast models with casting delays - Yusuf, Muhammad Erlangga Maulana; Karlina, Elin; Hasratiningsih, Zulia (Universitas Padjadjaran, 2014)
Introduction: Dimensional stability of alginate impression is important to obtain an accurate cast. This study was to find the linear dimensional changes of the cast made from delayed pour high stability alginate impression after 5 days. Methods: This experimental laboratory study used 20 samples, divided into 4 groups. First and third group were the generated cast produced by immediately pour into high stability and conventional alginate impressions. Second and fourth group were the generated cast produced by delayed pour into high stability and conventional alginate impression for 5 days in storage with 100% humidity. Dimensional changes were measured on the upper part of the cast from buccal-lingual and mesial-distal direction beside measuring on the outer distance between the upper cast used Mitutoyo digital caliper scaled 0.01 mm. The data were analyzed using ANOVA (α = 0.05).Results: Mesial-distal (a) diameter average of group I, II, IV were respectively 8.410 mm, 8.520 mm, and 8.620 mm, compared with III as control was 8.420 mm. Meanwhile, diameter averages of mesial-distal (b) were 8.314 mm, 8.416 mm, 8.513 mm, and 8.315 mm. The averages of distance between each teeth (c) were 13.312 mm, 13.240 mm 13.191 mm, and 13.316 mm. The diameter averages of buccal-lingual (d) were 8.411 mm, 8.530 mm, 8.608 mm and 8.410 mm. The diameter averages of buccal-lingual (e) were 8.350 mm, 8.441 mm, 8.524 mm, and 8.340 mm. ANOVA test of the results of distance measurements between teeth (c) produces a calculated F value of 147.850, higher than the F table value (3.239). There were significant diferencess dimensional changes on gypsum cast made from high stability alginate impression and then poured after 5 days. Conclusion: There were diferencess linier dimensional changes on gypsum cast made from high stability alginate impression and then poured after 5 days.